Electroconvulsive therapy for Patients with Intellectual Disability. When and how? - F. Azevedo; R. André; I. Donas-Boto; D. Jeremias; C. Almeida (European Psychiatry, 2022)
Introduction Intelectual disability is an illness with an important burden on patients and caregivers, especially when severe and when comorbidities such as other psychiatric disorders are present. There are case reports of treatment resistant self-aggression, agitation, epilepsy, catatonia and psychosis successfully treated with electroconvulsive therapy although controlled studies were not found.